Graviditas Dan Status Gizi: Kaitannya Dengan Hiperemesis Gravidarum - Handayani, Ayu Mustika; Kurnia Pratama, Rini Mustikasari; Riyanti, Endang (Bunda Edu-Midwifery Journal (BEMJ), 2020)
The incidence rate of hyperemesis gravidarum in Indonesia in 2016 is 1.5-3% of the total number of pregnant women (SDKI, 2016). Mostof the causes of maternal death are bleeding 70-80% experiencing morning sickness and as much as 25.2%, infection 11.1%, sepsis 15%. This study aims to find out the relationship of Gravidity and nutritional status with the incidence of hyperemesis gravidarum in pregnant women PMB Rosmala Aini In 2020. The research method used is analytical with the design of Case control 1:1. The study sample is pregnant women in PMB Rosmala Aini Kota Jambi which numbered 112 people. Research shows the risk gravidarum will experience hydilution of gravidarum by 0,495 on value (p-0,315) and undernutrition would have hylaxative gravidarum by 0,378 on value (p-0,000).